Readiness for Studens in Following Courses - Subagyo Subagyo; Ardi Widiyatmaka (Jurnal Taman Vokasi, 2019)
Abstracts. This study aims to identify the readiness of students in attending lectures. The background of the research starts from every time they teach their presence is not on time, when the bell rings only a few people who come after a few moments and then only one by one comes and some even before the end of class. As the subject of the study were students of Mechanical Engineering Education, Faculty of Teacher Training and Education, Sarjanawiyata Tamansiswa University who were considered to have awareness of obligations as students and as the object was their readiness to study. The research data were obtained based on observations and completed with questionnaires. The results were analyzed qualitatively, then triangulated against lecturers who were considered to understand the condition of students. The results showed that most students were less prepared to attend lectures, in the form of physical readiness, psychological readiness, and material readiness. The research output is information about the steps needed by the study program at the beginning of the year for new students to develop a more conducive academic atmosphere, and this information will be published in the journal Taman Vokasi.